Analisis Metode Penggalian Batuan Berdasarkan Kriteria Indeks Kekuatan Batu (Franklin) di Site Penambangan Batu DolomitePT. Bakapindo, Jorong Durian, Nagari Kamang Mudiak, Kecamatan Kamang Magek, Kabupaten Agam, Provinsi Sumatera Barat - Wahyu Kurniawan; Bambang Heriyadi (Departemen Teknik Pertambangan FT UNP, 2018)
PT.Bakapindo is engaged in dolomite mining. The mining method applied is the Open Pit quarry method. Currently the mining process is carried out by PT. Bakapindo applies the blasting method to release dolomite rock from its parent rock. In determining the right method for dismantling material, it is necessary to study rock capability. In this study, the method applied to determine the suitable excavation method is by Franklin's rock strength index criteria chart. The data used in the study are discontinuity field conditions taken with the scanline system and rock samples used to test rock strength by means of Point Load Index. Total data on discontinuity field conditions measured in rock mass is 201 data. The results of the point load index test obtained the Franklin (Is) average index value of 4.740MPa. Based on the results of the analysis of rock mass conditions at PT. Bakapindo found that rock mass rating (RMR) of 67 was classified as class II (Good rock), the fracture index value was 0.091m. Based on Franklin's rock strength index criteria graph, it can be concluded that suitable excavation methods are carried out at PT. Bakapindo is byblasting cracks.Keywords: mining method, Index Franklin, rock mass rating (RMR) , Discontinuiy, Point Load Index